Pronunciation French To Improve Your Speaking Skills French Language Students-Based Media Video - Adawi, Rabiah; Polili, Andi Wete; Ghofur, Abdul (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The purpose of this research is to develop the Pronunciation En Dialogue textbook, in the form of a physical book equipped with an electronic book containing audio video in one click and to measure the feasibility of the media products that can be used as a medium of learning conversational skills in French, so as to improve the ability of students of French Language Education UNIMED. We hope to increase the ability of these students to speak the French language as a result of using textbooks and instructional videos that are developed. These textbooks will be published with their indexes in international journals. By using the six stages of research and development (research and development), namely; 1.the analysis of the potential and problems, 2.data collection, 3.the design of the product, 4.design validation, 5.product revision, and 6.product trials, this study was able to analyze the potential and problems through the use of observation and questionnaires. Researchers tested the product to the students of French language education UNIMED using questionnaires,Â  a process used to develop and validate products of education, learning model in the form of videos and books as textbooks. Data were collected through study documentation and observation of learning. Consequently, this study produced a video media to improve the pronunciation of French Language Speech of the French language students. Study limitations included a limited research in the area of pronunciation of French in French FBS UNIMED Students. This research is important because of its ability to aid the learning process of French language from the beginning to the end.